Aplikasi Visualisasi Kamar Kost Menggunakan Teknologi Virtual Reality Berbasis Android - Thio Philoes; Alexander Waworontu (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to produce room visualization application for kost using virtual Reality (VR) technology, in order to make it easier for someone not to come to room kost. This application is used by some people who want to see the room kost and the items used in the visualization room kost. Researchers develop applications using the multimedia development Life cycle (MDLC) method. Application development uses unity, the SDK to support virtual reality into unity and Google SketchUp. The result of this research is an Android based application with APK file format that can be run on a smartphone (smartphone) with a gyroscope sensor and a minimum operating system Android 4.4 KitKat and above.